Development of an auto-interchangeable multi-pinhole array for confocal laser scanning microscopy systems using precision laser processing. (August 2019) - Boutilier, Richard M.; Ahn, Yoon Joon; Park, Jae Sung; Lee, Ho
Highlights: Laser micro-machining quality improved by lower power and higher number of passes. Near-perfect array alignment due to using its linear actuator during manufacture. Simple pinhole exchange enabled by high-resolution low-backlash linear actuator. Abstract: Confocal laser scanning microscopy systems rely on a pinhole placed at the confocal point to act as a spatial filter. The diameter of the pinhole critically affects both the brightness and resolution of the imaging. Furthermore, different imaging conditions, such as sample type, depth of the sample, wavelength of the signal, and its inherent emission or reflection strength, require varying balances between the brightness and optical resolution for optimal observability. However, exchanging the pinhole, and its subsequent alignment, is often a time consuming challenge when implemented in customized systems. These systems are important since they are often used in studies for which commonly available ones lack sufficient capabilities. As such, we have developed an auto-positioning interchangeable pinhole array, manufactured via a patented laser machining process and designed for convenient implementation in confocal laser scanning microscopy systems and we demonstrate its effectiveness and versatility.